Insect temperature–body size trends common to laboratory, latitudinal and seasonal gradients are not found across altitudes. (11th January 2018) - Horne, Curtis R.; Hirst, Andrew G.; Atkinson, David
Abstract: Body size affects rates of most biological and ecological processes, from individual performance to ecosystem function, and is fundamentally linked to organism fitness. Within species, size at maturity can vary systematically with environmental temperature in the laboratory and across seasons, as well as over latitudinal gradients. Recent meta‐analyses have revealed a close match in the magnitude and direction of these size gradients in various arthropod orders, suggesting that these size responses share common drivers. As with increasing latitude, temperature also decreases with increasing altitude. Although the general direction of body size clines along altitudinal gradients has been examined previously, to our knowledge altitude–body size (A–S) clines have never been synthesised quantitatively, nor compared with temperature–size (T–S) responses measured under controlled laboratory conditions. Here we quantitatively examine variation in intraspecific A–S clines among 121 insect species from 50 different global locations, representing 12 taxonomic orders. While some taxa were better represented in the literature than others, our analysis reveals extensive variation in the magnitude and direction of A–S clines. Following the assumption that temperature on average declines by 1°C per 150 m increase in altitude, order‐specific A–S clines in the field appear to deviate from laboratory T–S responses. Specifically, the magnitude of A–S clines and T–S responses are more closely matched in some taxonomic orders (e.g. Diptera) than others (e.g. Orthoptera). These findings contrast with the strong co‐variation observed between latitude‐size clines and T–S responses, and between laboratory and seasonal T–S responses. The lack of clear size relationships with elevation, and hence temperature, is likely due to the counteracting effects of other major drivers with altitude, including season length and oxygen partial pressure. Switches in voltinism within species across altitude, and the dispersal of individuals across different elevations, may also obscure trends. A plain language summary is available for this article. Abstract : Plain Language Summary